Kekerasan Perempuan dalam Novel "موسم الهجرة الى الشمال" (Teori Postkolonial Gender) - Muhammad Attila Rifiananda (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This research analyzes the forms of physical and psychological violence against female characters in the novel Mausim al-Hijrah ila al-Syamāl (Season of Migration to the North) by Tayeb Salih using the perspective of Gayatri Chakravorty Spivak's subaltern theory. The research method used is descriptive qualitative with a library research approach. The primary data source is the original Arabic text of the novel. Data collection techniques employ reading and note-taking methods, while data analysis uses the Miles and Huberman model. The research findings reveal ten forms of violence experienced by female characters, namely sadomasochistic sexual violence, murder during sexual intercourse, manipulation through orientalist imagination, destruction of subjective autonomy, forced marriage leading to suicide, domestic violence, psychological trauma, social isolation, violence of representation in male narratives, and silent death as the only space for subjectivity. This research concludes that violence against women in the novel reflects the intersection of colonial legacy and local patriarchy, while also confirming Spivak's thesis that the subaltern cannot speak because women's voices are always silenced by mechanisms of epistemic violence and unethical representation.